ERODIBILITY ANALISYS OF THE CAMORIM TRAIL – STATE PARK OF PEDRA BRANCA (PEPB-RJ) – BRAZIL - Beatriz Pereira Triane; Vivian Castilho da Costa (Sociedade & Natureza)
In the last years, there was a growth on activities linked to ecotourism in Brazil and therefore the protected areas became a great attraction to the people that seek this kind of leisure alternative.The increase of the number of people looking for living in cohabition with nature and with different activities connected this sector, now makes a discussion about impacts caused by the visitation extremely important, mainly in protected areas.The trails that are more used for recreational means, allows access to attractions and inner areas of protected areas and, in consequence, they possess considerable importance in the planning and management for public use. As defined by COSTA (2004, p.9): "the trails should be creteriously located, planned, builted and managed in way to allow the conservation of the natural resources and the accomplishment of appropriated visitors contact".